Analysis of Pregnancy Case with Termination of Caesarean Section at PKU Muhammadiyah Gombong Hospital - Indriyastuti, Hastin Ika; Sofiana, Juni; Astuti, Dyah Puji; Rahmadhani, Wulan (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2021)
Caesarean section (C-section) is a surgical procedure to deliver a baby through incisions in the abdomen and uterus as spontaneous delivery cannot be carried out. C-sections have increased in number from time to time. Even, in Indonesia, C-section shows an increase with varied percentages among provinces. This study aims to identify the determinant factors of delivery with the termination of caesarean section. This study used retrospective data. It involved a total sample of 372 respondents determined with a total sampling method. Data were collected by observation and then the data were analyzed using the Chi-square test. Results: Based on the results of this study, the p-value reached 0.048 for gestational age, 0.014 for maternal age, 0.004 for comorbidities, and 0.003 for the history of C-Section. The results indicate that there was a relationship between gestational age, maternal age, comorbidities, and history of CS with C-Section delivery. Conclusion in this research was The determinant factors of termination of delivery with C-Section covered the mother's age, gestational age, comorbidities or complications during pregnancy, and history of C-Section.  Persalinan sectio caesarea (SC) merupakan persalinan buatan melalui dinding rahim untuk mengeluarkan janin karena kalau dilakukan persalinan secara spontan tidak bisa dilakukan, persalinan ini dari waktu ke waktu mengalami peningkatan jumlahnya. Dan saat ini operasi sesar di Indonesia menunjukkan peningkatan dan persentasenya bervariasi antar provinsi. Tujuan dari penelitian ini untuk mengidentifikasi determinan kehamilan dengan terminasi operasi sesar Metode : penelitian ini menggunakan retrospektif data. Totalsampel pada penelitian ini adalah 372 responden di ambil dengan metode total sampling. Data di ambil dari observasi dandi tes menggunakan chi-square test. Hasil : berdasarkan dari hasil penelitian ini di dapatkan bahwa p-value pada umur kehamilan sebesar 0.048, umur ibu 0.014, penyakit penyerta 0.004 dan riwayat SC 0.003. menyatakan bahwa terdapat hubungan antara umur kehamilan, umur ibu, penyakit penyerta dan riwayat SC dengan persalinan SC. Kesimpulan : Faktor pendorong terjadinya terminasi persalinan dengan section caesaria (SC)adalah karakteristik umur ibu, umur kehamilan, penyakit penyerta atau penyakit penyulit selama kehamilan dan ibu dengan riwayat SC memiliki peluang besar terhadap terjadinyapersalinan dengan operasi sesar.